PALATOPLASTY PROCEDURE WITHOUT LATERAL RELAXING INCISION- AN INNOVATIVE APPROACH - Mishra, Biswajit; Dash, Sonika; Barman, Diplina; Chhaya; Rani, R Padmini; Banerjee, Shruti (International Journal of Psychosocial Rehabilitation, 2020)
Aims and objectives: Aim of palatoplasty is to optimize the speech and feeding, closure of the oronasal passage without having any adverse effect on maxillary growth. Scar produced after palatoplasty is a well known risk factor for adverse maxillary growth. Methods: Between July 2016 and September 2018, palatoplasty was performed in 22 patients with cleft palate of varying grade (median age 47 month; range, 10 month -8 year). Entire palate was closed in a single setting. Nasal layer closure, intravelar veloplasty and oral layer closure was done in succession. A straight line closure was performed on both the nasal and oral sides. The incision on the soft palate was given at the junction of nasal mucosa and oral mucosa. It was extended anteriorly to the hard palate beyond posterior nasal spine. Mucoperiosteal flap was elevated by subperiosteal undermining in the entire palatine bone. No relaxing incision was given on the lateral side. Oral layer closure started from posterior portion and entire palate was closed in the midline without any lateral relaxing incision. Patients were followed up for 6 months to 1.2 years. Results: There was no incidence of flap necrosis. All palate had good healing. There was no other complications such as bleeding, wound dehiscence, fistula or hanging palate . Conclusions: Though this procedure has a learning curve it is a useful technique for preventing adverse maxillary growth.